The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1074/jbc.m113.455006
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric Tn Antigen on Syndecan 1 Produced by ppGalNAc-T13 Enhances Cancer Metastasis via a Complex Formation with Integrin α5β1 and Matrix Metalloproteinase 9

Abstract: Background: ppGalNAc-T13 is up-regulated in high metastatic murine lung cancer cell lines. Results: Trimeric Tn on Syndecan 1 forms a complex with integrin ␣5␤1 and MMP-9, leading to cell adhesion and cancer metastasis. Conclusion: Reduction of GM1 induces ppGalNAc-T13 expression, and its product trimeric Tn enhances metastasis via integrins. Significance: A novel key molecule in cancer metastasis is identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…In addition, syndecan-1 can act as regulator of a v b 3 and a v b 5 integrin activation [15,17]. Modulation of a 5 b 1 integrins by syndecan-1 was also reported during focal adhesion formation and migration [18][19][20]. Interestingly, the latter pathway can either enhance or suppress these processes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, syndecan-1 can act as regulator of a v b 3 and a v b 5 integrin activation [15,17]. Modulation of a 5 b 1 integrins by syndecan-1 was also reported during focal adhesion formation and migration [18][19][20]. Interestingly, the latter pathway can either enhance or suppress these processes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of a 5 b 1 integrins by syndecan-1 was also reported during focal adhesion formation and migration [18][19][20]. Interestingly, the latter pathway can either enhance or suppress these processes [18][19][20]. Further, activation of focal adhesion kinase (FAK) and Rho GTPase has been implicated in syndecan-1-mediated effects on cell migration [16,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, Galnt13 was also identified as an up-regulated gene in high metastatic mouse lung cancer cell lines (Matsumoto et al 2012). In this case, the molecular basis of aggressive behavior was explained by GalNAc-T13 leading to formation of trimeric Tn antigen on syndecan-1 (Matsumoto et al 2013). Recently, high expression of GalNAc-T13 was also demonstrated in human lung cancer and this was correlated with poor prognosis, suggesting that this enzyme may represent a prognostic factor (Nogimori et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…However, it was previously reported that GalNAc-T13 differs in peptide substrate preferences from GalNAc-T1, and in particular with respect to important substrates such as Syndecan . We are interested in GalNAc-T13 because of its potential involvement in cancer biology (Berois et al 2006b;Matsumoto et al 2012;Matsumoto et al 2013;Nogimori et al 2016). Using microarray gene expression analysis in a metastatic xenograft-derived cell model of human neuroblastoma (so-called IGR-N-91), we found that GALNT13 was the most strongly up-regulated gene (12-fold) in metastatic malignant neuroblasts compared with primary tumor xenograft (Berois et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the hypothesis above, it is also possible that there may exist some other proteins that mediate the functions of ppGalNAc-T13 in neurogenesis and that these proteins could be specifically glycosylated by ppGalNAc-T13. Besides PDPN, both sydecan-3 and syndecan-1 have been found to be the substrates of ppGalNAc-T13 (28,61,62), and sydecan-3 has been reportedly involved in axon guidance, neuralmigration,andneuronalplasticity (63,64).Meanwhile,O-glycosylation modifications have also been observed on several neuron-specific transmembrane or matrix proteins such as p75 (neurotrophin receptor), amyloid precursor protein, neural cell adhesion molecule, and testicans (65)(66)(67)(68), although little is known about their functions in neural development. Clearly, further study is needed to clarify the mechanisms of the distinct roles of ppGalNAc-T13 in neural differentiation.…”
Section: The Significance Of Ppgalnac-t13 and Pdpn In Neurogenesismentioning
confidence: 99%